PENGARUH PROMOSI DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA PT. PALMANCO INTI SAWIT - Desi Desi; Elisabet Tambunan (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
This study aims to determine and analyze the effect of promotion and product quality on purchasing decisions at PT. Palmanco Inti Sawit. The formulation of the problem in the study was